"It Seems Like I'm Doing Something More Important"-An Interpretative Phenomenological Analysis of the Transformative Impact of Research Experiences for STEM Students with ADHD - Arash E. Zaghi; Alexander Grey; Alexandra Hain; Connie M. Syharat (MDPI AG, 2023)
Recent studies have suggested a link between attention deficit hyperactivity disorder (ADHD) and increased creativity and ingenuity. Clinical work suggests that individuals with ADHD generally gravitate toward exploratory rather than exploitative thinking. Yet, these theories have not been tested in the field. This paper is a case study of a transformative undergraduate summer research program that allows engineering students with ADHD to spend 10 weeks in engineering labs at a research-intensive (R1) university. The program intends to show that students with ADHD can excel in engineering and STEM fields when placed in research environments that align with their natural cognitive processes and preferences. Using an interpretative phenomenological analysis (IPA) on post-program participant interviews, this paper suggests that engineering students with ADHD perceive that they learn more effectively when given the opportunity to explore academic material via hands-on research. The traditional structure of STEM education, with its focus on lectures and rigid curricula, causes significant harm to these students, leading to struggles, anxiety, and even thoughts of dropping out. In contrast, the research environment appears to foster creativity and motivation in students with ADHD, as it allows for exploration, provides real-world problem-solving opportunities, and offers tangible, hands-on experiences. This paper highlights the need for a paradigm shift in engineering pedagogy to better engage with and retain this neurodiverse student population and fully harness their creative potential.